The adjustment of pavement deflections due to temperature variations - Pais, Jorge C. (2020)
One of the most important steps in the rehabilitation of flexible pavements is the evaluation of their bearing capacity, which is used to assess the moduli of the pavement layers. The evaluation of the bearing capacity is usually carried out by measuring pavement deflections using a Falling Weight Deflectometer (FWD). This evaluation is undertaken in equally spaced points, usually 100 metres apart, with temperature variations throughout the day. Due to the viscoelastic behaviour of the asphalt layers, these FWD measurements are influenced by the pavement temperature, and the moduli can only be compared if they correspond to the same temperature. Thus, this work develops a model to adjust the pavement deflections to a reference temperature based on the characteristics of the pavement; namely: the asphalt layer thickness, subgrade stiffness, the distance between the FWD sensors, the load magnitude, and the pavement temperature.